Neutron radiography analysis of a hydride-based hydrogen storage system. (21st December 2015) - Baruj, A.; Borzone, E.M.; Ardito, M.; Marín, J.; Rivas, S.; Roldán, F.; Sánchez, F.A.; Meyer, G.
Abstract: A hydrogen container based on the use of a hydride forming material (LaNi5 ) has been specifically designed for performing in-situ Neutron Imaging experiments. The device allows following the process of heat-induced hydrogen release from the initially fully hydrided material. A reaction front forms in the material around the central heater. As the experiment proceeds, the front expands radially. Later on, heat conduction by the container walls produces the decomposition of the hydride in contact with them. As a consequence, and for the implemented geometry, the front advances at an almost constant radial speed. A simple analysis of the images contrast allows the quantification of the ratio between the hydride and metal phases for the complete experiment. Highlights: Hydrogen release from a storage tank has been studied by means of Neutron Radiography. The images show the formation of a hydride decomposition front in the material. Phase fraction values were determined by analyzing transmittance levels. Neutron Radiography is a useful tool for following the dehydriding reaction dynamics.